Competency Improvement Novice Lecturer (PKDP) - Muhamad Uyun (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Competence is one of the objectives of a professional education program. Competency improvement is an effort to develop knowledge, skills, and attitudes that every teaching staff must carry out to get maximum results. The level of professionalism of lecturers needs to be improved to carry out their duties professionally. One way to improve the learning process is by increasing competence, especially in writing accredited articles and understanding the use of Mendeley. Based on the situation analysis, there is still a lack of understanding competence of novice lecturers at UIN Raden Fatah Palembang. Therefore it is the purpose of this activity to improve the competence of novice lecturers in writing accredited articles and understanding the use of Mendeley. The implementation method is carried out for 16 hours. The training was held for two days on Wednesday-Thursday, December 21-22, 2020, at the Santika Premiere Hotel Palembang by conducting an initial survey using google form internet media. The number of participants was 100 participants consisting of lecturers of UIN Raden Fatah Palembang. The first material was about writing accredited articles for novice lecturers. The second material is about how to understand the use of Mendeley. As a result of this training, the participants understood the writing of accredited articles and the use of Mendeley.